The Black Arts Movement and the Black Panther Party in American Visual Culture - Morgan, Jo-Ann, author.
1 online resource (232 pages)
Keywords: This book examines a range of visual expressions of Black Power across American art and popular culture from 1965 through 1972. It begins with case studies of artist groups, including Spiral, OBAC and AfriCOBRA, who began questioning Western aesthetic traditions and created work that honored leaders, affirmed African American culture, and embraced an African lineage. Also showcased is an Oakland Museum exhibition of 1968 called "New Perspectives in Black Art," as a way to consider if Black Panther Party activities in the neighborhood might have impacted local artists’ work. The concluding chapters concentrate on the relationship between selected Black Panther Party members and visual culture, focusing on how they were covered by the mainstream press, and how they self-represented to promote Party doctrine and agendas.